Kemampuan literasi informasi peneliti dalam penulisan karya ilmiah di Loka Litbangkes Pangandaran - Dani Arif Cahyadi (Universitas Padjadjaran, 2018)
The productivity of scientific papers in disseminating research results, mastering basic tasks and competencies in functional positions does not necessarily make the researcher a literate person. Researchers at the Loka Litbangkes, Pangandaran still indicated the existence of issues related to the mastery of information literacy especially in writing scientific papers. The information literacy capabilities of researchers are not yet known comprehensively and deeply, so research is needed to uncover it. This study used a descriptive qualitative approach. The purpose of the study was to obtain a clear picture of the information literacy abilities of researchers, especially in scientific writing. The conceptual research framework to study the information literacy skills of researchers used the SCONUL Seven Pillars Information Literacy Research Lens. Informants were three researchers and colleagues at the Loka Litbangkes, Pangandaran who were determined based on purposive sampling. Results showed that researchers did not master information literacy skills yet. First-level researchers indicated that they did not fully master the Plan, Gather and Evaluate competencies. Middle-level researchers were indicated that they did not master the competencies of Plan, Gather, Evaluate and Present. Whereas the high-level researchers were indicated that they did not fully master the Plan, Gather, Evaluate, Manage and Present competencies. In conclusion, the researcher's information literacy skills are constrained by the lack of participation in information literacy training, limitations and irregularities in library collections, unavailability of access to Scopus indexed international journal databases, lack of science communication networks motivations and limited English proficiency.